The spa Typing and Characterization of Nasal Carriage Methicillin-resistant Staphylococcus aureus Isolates From Healthy Children - Shaghayegh Rezai; Reza Valadan; Fatemeh Ahangarkani; Mohammad Sadegh Rezai (Mazandaran University of Medical Sciences, 2020)
Background: The Methicillin-resistant Staphylococcus aureus (MRSA) strains cause wide spectrum infections in hospitals and are responsible for the majority of the community-acquired infections. The emergence of community-acquired MRSA in patients without risk factors represents a high risk for public health.  Objectives: In this study, we aimed to molecular typing the nasal carriage MRSA strains harbored mecA gene isolated from healthy children living in the North of Iran and also to determine the pattern of vancomycin susceptibility in these isolates.   Methods: The MRSA strains were identified using standard microbiological and molecular procedures. The antibiotic susceptibility test was performed according to the clinical and laboratory standards institute. The MRSA strains were characterized by spa typing.  Results: In total, 14 different patterns of spa genes were obtained from MRSA isolates in this study, which included t790 (23.07%), t2962 (15.38%), t267 (15.38%), t159 (7.69%) and t701, t094, t1816, t11332, t937, t2135, t180, t160 [1 (3.84%) isolate per each type]. The rate of resistant isolates to cefoxitin, , cefalotin, clindamycin, cefazolin, co-amoxiclav, co-trimoxazole, and cephalexin antibiotics were 69.23%, 100%, 46.15%, 96.15%, 100%, 3.48%, and 100%, respectively. In total, six (23.07%) revealed vancomycin-intermediate resistant phenotype and five (19.23%) isolates revealed vancomycin-resistant S. aureus phenotype. Conclusions: This study showed the different variants of MRSA strains based on molecular typing, among healthy children. Continuous surveillance studies to monitor MRSA should be encouraged to gain a better understanding of the circulating MRSA strains and prevent community spread of this pathogen.